Opening the gender diversity black box: causality of perceived gender equity and locus of control and mediation of work engagement in employee well-being - Sharma, Radha R.; Sharma, Neha P. (Frontiers in Psychology, 2015)
The study is aimed at assessing the role of perceived gender equity and locus of control in employee well-being at the workplace and ascertaining if work engagement mediates between perceived gender equity, locus of control, and employee well-being (measured through optimism, general satisfaction with life and work, and executive burnout). Adopting a personal survey method data was collected from 373 managers (both males and females) from the public and private sectors representing manufacturing and service industry in India. The study bridges the knowledge gap by operationalising the construct of perceived gender equity and studying its role in the work engagement and employee well-being. Conceptualization of the well-being in an unconventional way covering both the positive and the negative aspects extends the understanding of the emerging concept of well-being. It has practical implications for talent management and work engagement besides promoting gender equity at the workplace for employee well-being. It opens vistas for the gender based theory and cross cultural research on gender equity.